Special collection on mobile mixed reality 2019 update - Thomas Cochrane; Vickel Narayan; James Birt (Association for Learning Technology, 2020)
This special collection of Research in Learning Technology explores the development of the state of the art of Mobile Mixed Reality (MMR) in education. The special collection was established in 2018 to provide research-informed exploration of this emergent and rapidly developing arena of educational technology through the lens of Scholarship Of Technology Enhanced Learning (SOTEL). The special collection update for 2019 includes four articles that cover self-efficacy and motivation of MMR users, analysis of student experiences of MMR, and a selection of case studies on designing and implementing MMR in educational contexts. The range of articles illustrates the further development of MMR as a platform for designing authentic learning environments in both formal and informal learning situations. The articles also highlight attempts to address the issue identified in the 2018 collection of a general lack of engagement with new learning theories and models in the use of MMR to design transformative learning experiences.